(untitled) - Getis, Arthur (New York, 2004)
The field of spatial econometrics has come to include the methods and models that deal with estimation and testing problems encountered when attempting to implement regional economic models. Those problems are often characterized by the difficulties associated with assessing the importance of spatial dependence and spatial heterogeneity. This book includes contributions on spatial proximity, spatial patterning and in particular the spatial association (dependence) contained in local map patterns.
Keywords: Geography,Spatial analysis (statistics),Econometrics; Statistical methods,Congresses,Congresses,Congresses